2016
DOI: 10.1597/15-053
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Symmetry in Children with Unrepaired Cleft Lip: Defining a Standard for the Three-Dimensional Midfacial Reference Plane

Abstract: Raters can agree on the 3D midfacial reference plane in children with unrepaired CL using digital surface mesh. The Deformation method performed best among computer-based methods evaluated and can be considered a useful tool to carry out automated measurements of facial symmetry in children with unrepaired cleft lip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 47 publications
0
33
0
2
Order By: Relevance
“…Jia Wu et al showed that the angle difference between the two planes is easily perceived when it is more than 6° [23]. The angle error between the WPA SRP and the professional plane was less than 2°, which indicates that the accuracy of the WPA SRP was almost equal to that of the professional plane and therefore had better clinical suitability than the PA SRP.…”
Section: Discussionmentioning
confidence: 99%
“…Jia Wu et al showed that the angle difference between the two planes is easily perceived when it is more than 6° [23]. The angle error between the WPA SRP and the professional plane was less than 2°, which indicates that the accuracy of the WPA SRP was almost equal to that of the professional plane and therefore had better clinical suitability than the PA SRP.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al showed that the angle difference between the two planes is easily perceived when it is > 6° [23].…”
Section: Analysis Of Fai Errormentioning
confidence: 99%
“…The study analyzed the reduction of the asymmetry index, as described by Wu et al, because of the simplicity and high reproducibility of the protocol proposed by the authors [14].…”
Section: Case Reportmentioning
confidence: 99%